Cretaceous Evolution of the Central Asian Proto‐Paratethys Sea: Tectonic, Eustatic, and Climatic Controls. Issue 9 (2nd September 2020) - Kaya, Mustafa Yücel; Dupont‐Nivet, Guillaume; Proust, Jean‐Noël; Roperch, Pierrick; Meijer, Niels; Frieling, Joost; Fioroni, Chiara; Özkan Altiner, Sevinç; Stoica, Marius; Aminov, Jovid; Mamtimin, Mehmut; Guo, Zhaojie
Abstract: The timing and mechanisms of the Cretaceous sea incursions into Central Asia are still poorly constrained. We provide a new chronostratigraphic framework based on biostratigraphy and magnetostratigraphy together with detailed paleoenvironmental analyses of Cretaceous records of the proto‐Paratethys Sea fluctuations in the Tajik and Tarim basins. The Early Cretaceous marine incursion in the western Tajik Basin was followed by major marine incursions during the Cenomanian (ca. 100 Ma) and Santonian (ca. 86 Ma) that reached far into the eastern Tajik and Tarim basins. These marine incursions were separated by a Turonian‐Coniacian (ca. 92–86 Ma) regression. Basin‐wide tectonic subsidence analyses imply that the Early Cretaceous sea incursion into the Tajik Basin was related to increased Pamir tectonism. We find that thrusting along the northern edge of the Pamir at ca. 130–90 Ma resulted in increased subsidence in a retro‐arc basin setting. This tectonic event and coeval eustatic highstand resulted in the maximum observed geographic extent of the sea during the Cenomanian (ca. 100 Ma). The following Turonian‐Coniacian (ca. 92–86 Ma) major regression, driven by eustasy, coincides with a sharp slowdown in tectonic subsidence during the late orogenic unloading period with limited thrusting. The Santonian (ca. 86 Ma) major sea incursion was likely controlled by eustasy as evidenced by the coeval fluctuations in the west Siberian Basin. An early Maastrichtian cooling (ca. 71–70 Ma), potentially connected to global Late Cretaceous trends, is inferred from the replacement of mollusk‐rich limestones by bryozoan‐ and echinoderm‐rich limestones. Key Points: A new regional chronostratigraphic framework is provided for the Cretaceous sea incursions in the Tajik and Tarim basins in Central Asia The origin, extent, and evolution of the proto‐Paratethys in Central Asia are connected to the effects of far‐field tectonics and eustasy Early Maastrichtian cooling is identified by lithofacies change from mollusk‐rich to bryozoan‐ and echinoderm‐rich limestones